Generation of OAM waves with circular phase shifter and array of patch antennas. Issue 6 (1st March 2015) - Wei, Wenlong; Mahdjoubi, Kourosh; Brousseau, Christian; Emile, Olivier
Abstract : The design of an 'orbital angular momentum (OAM) antenna' based on an original phase shifter and power divider combination at 2.5 GHz is presented. A prototype is manufactured and characterised based on return loss, radiation and phase patterns. Both simulation and experimental results evidence the properties of waves carrying OAM. This OAM antenna is simple, compact and easy to realise, which makes it suitable for radio communications and radar applications.